Evaluation of factors affecting real‐time PCR performance for diagnosis ofEntamoeba histolyticaandEntamoeba disparin clinical stool samples. Issue 9 (September 2015) - Forsell, Joakim; Koskiniemi, Satu; Hedberg, Ida; Edebro, Helén; Evengård, Birgitta; Granlund, Margareta
Abstract : N/A: Although PCR offers the potential for sensitive detection of parasites there are several pitfalls for optimal performance, especially when DNA is extracted from a complex sample material such as stool. With the aid of a sensitive inhibitor control in a duplex real‐time PCR (qPCR) for identification of Entamoeba histolytica and Entamoeba dispar we have evaluated factors that influenced the performance of the qPCR and have suggested a rationale to be used in the analysis of clinical samples. Pre‐PCR processing was found to be of outmost importance for an optimal amplification since inhibitors caused false‐negative results when higher amounts of sample were used. Stool sampling with a flocked swab (ESwab, Copan), yielding on average 173 mg, gave positive qPCR results in samples with cysts of E. dispar that were negative in serially diluted stool samples. The degree of inhibition found varied between samples and was not an on‐off phenomenon. Even low‐grade inhibition, shown as an increase of two cycles in the qPCR for the inhibitor control, could lead to false negativity in samples with low amounts of parasites. Lack of amplification in the qPCR due to inhibition could be overcome by dilution of the extracted DNA by 1/10–1/20. We also describe the use of guanidinium thiocyanate buffer for transport and storage of samples as well as a time‐saving semi‐automated DNA extraction method in an Arrow instrument (Nordiag) preceded by bead beating.